Influencia de los factores personales y laborales en la calidad de servicio de las tutoras, de la cuna maternal "josefina pinillos de larco". trujillo, año 2013 - Arroyo Achuy, Paola Ingrid (2014)
This research is focused on explaining the INFLUENCE OF PERSONAL AND LABOR QUALITY FACTORS IN THE SERVICE OF THE CRADLE MATERNITY tutors “JOSEFINA PINILLOS DE LARCO". TRUJILLO. YEAR 2013 . This study was conducted with a total of 36 people , consisting of 10 tutors , 21 mothers , and 5 administrative staff and workers of that institution . Statistically, Ethnographic and Phenomenological Analytic and Synthetic: To obtain the data, methods were used. The observation, survey and review of literature sources: So the following techniques were also used. Through instruments: questionnaire, observation and interview guides. This has been based on the following theoretical approaches: Approach Human Scale Development, Human Rights Focus, Focus management total quality management. Since research has proven the hypothesis, concluding that personal and occupational factors, adversely affect the quality of service of the mentors of the Cradle Maternal "Josefina Pinillos Larco".